ASEAN COOPERATION IN ERADING CRIMINAL ACTS OF TERRORISM IN SOUTHEAST ASIAN AREA - Rusito Rusito; Kaboel Suwardi; Doni Adi Supriyo (Universitas Pendidikan Ganesha, 2020)
Today terrorism has become the most serious threat to humanity and civilization and has had a huge impact on all aspects of the life of the nation and state. At the regional level, Southeast Asia is a region facing serious challenges in the security sector. The problem of terrorism is a problem faced by many Southeast Asian countries. The number of terrorism incidents occurring in Southeast Asia has resulted in ASEAN being demanded to play a bigger role in solving this problem. The ASEAN Convention on Counter Terrorism (ACCT) was signed at the 12th ASEAN Summit in Cebu, Philippines, January 2007. This convention provides a strong legal basis for increasing ASEAN cooperation in the field of combating terrorism. Apart from having a regional character, ACCT is comprehensive (covering aspects of prevention, enforcement and rehabilitation programs) so that it has added value when compared to similar conventions. The harmonization of cooperation in the ACCT can be seen from the cohesiveness of ASEAN member countries in agreeing to the neutrality of defining terrorism as a common enemy and also counter-terrorism efforts by still adjusting to the principles of upholding human rights, international law and UN resolutions and without labeling certain communities as terrorist groups. The obstacles faced by ASEAN in eradicating criminal acts of terrorism in the Southeast Asia region are the ASEAN principle of non-intervention, ASEAN still focuses on social and cultural issues, domestic political conflicts in ASEAN Member countries such as Thailand and Myanmar and conflicts that occur among ASEAN member countries such as Indonesia and Malaysia in the case of borders and culture.